PEO-based solid electrolyte film and preparation method and application thereof

By introducing DFBOP and LLZTO into PEO-based solid electrolytes, a dense interface layer is constructed, which solves the problem of poor lithium stability and high-voltage compatibility, significantly improves the cycle stability and rate performance of lithium metal batteries, and realizes efficient ion transmission of electrolytes and the long-term stable operation of the battery.

CN119133589APending Publication Date: 2024-12-13ZHEJIANG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411201505.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The poor stability and high voltage compatibility of PEO-based solid electrolytes for lithium are caused by low ionic conductivity and electrode interface compatibility problems in their application in lithium metal batteries, which affects the cyclic stability and rate performance of the battery.

Method used

The combination of PEO-LiTFSI-DFBOP-LLZTO is used as the solid electrolyte film. A dense interface layer is constructed through the molecular coordination regulator DFBOP and the inorganic filler LLZTO to improve the uniform deposition of lithium and the ionic conductivity of the electrolyte, and reduce the intensity of the electrode interface. Decompose and enhance the mechanical properties of the electrolyte.

Benefits of technology

It significantly improves the cycle stability and rate performance of PEO-based solid lithium metal batteries, improves the ionic conductivity and electrochemical performance of the electrolyte, and ensures the long-term stable operation and high-voltage stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133589A_ABST
    Figure CN119133589A_ABST
Patent Text Reader

Abstract

The invention discloses a PEO-based solid electrolyte film and a preparation method and application thereof, the PEO-based solid electrolyte film comprises a polymer matrix and a lithium salt, the polymer matrix is selected from PEO, and the lithium salt is selected from LiTFSI; the PEO-based solid electrolyte film also comprises a molecular coordination regulator and a filler, the molecular coordination regulator is selected from DFBOP, and the filler is selected from LLZTO. According to the PEO-based solid electrolyte film disclosed by the invention, the problems of poor lithium stability and high-voltage compatibility of PEO-based solid electrolyte can be remarkably improved, and the cycling stability and rate capability of a PEO-based solid lithium metal battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a PEO-based solid electrolyte film and a preparation method thereof, and application thereof in solid-state lithium metal batteries. Background Art

[0002] At present, lithium-ion batteries have been shining in the fields of portable electronic devices, electric vehicles and large-scale grid energy storage due to their advantages such as high energy density, long cycle life and no memory effect. However, with the rapid development of electronic information and automobile industries, the limited energy density of lithium-ion batteries (<300Wh / kg) has been unable to meet the growing performance requirements, and is accompanied by more prominent safety hazards. Therefore, it is urgent to develop new battery systems with high energy density, high safety performance and long cycle life.

[0003] Using low-flash-point, non-flammable solid electrolytes to replace traditional organic liquid electrolytes and assemble them into solid-state lithium metal batteries is considered an effective strategy to solve the current dilemma of lithium-ion batteries. Therefore, solid-state lithium metal batteries have gradually become one of the strong candidates for high energy density, long cycle life and high safety energy storage and power battery technology. Among various solid electrolytes, polyethylene oxide (PEO)-based polymer electrolytes are favored by researchers due to their excellent mechanical flexibility, good interface contact and good flexibility in component design. However, PEO-based polymer electrolytes have been plagued by problems such as low ionic conductivity and poor electrolyte / electrode interface compatibility.

[0004] At present, the ionic conductivity of PEO-based electrolytes has been improved to a certain extent through the design and development of fillers, polymer structure design, and the introduction of plasticizers and other modification strategies, but the compatibility problem of the positive and negative electrode interfaces has not been well solved. Therefore, the development of a simple and efficient method for regulating the interface of PEO-based electrolytes has positive significance for promoting the development of PEO-based electrolytes and solid-state lithium metal batteries. Summary of the invention

[0005] In view of the problems of poor lithium stability and high-voltage compatibility of PEO-based solid electrolytes in the prior art, the present invention discloses a PEO-based solid electrolyte film, which can significantly improve the problems of poor lithium stability and high-voltage compatibility of PEO-based solid electrolytes, and significantly improve the cycle stability and rate performance of PEO-based solid-state lithium metal batteries.

[0006] The specific technical solutions are as follows:

[0007] A PEO-based solid electrolyte film, the raw material composition includes a polymer matrix and a lithium salt:

[0008] The polymer matrix is ​​selected from PEO, and the lithium salt is selected from LiTFSI;

[0009] The raw materials of the PEO-based solid electrolyte film also include a molecular coordination regulator and a filler. The molecular coordination regulator is selected from DFBOP, and the filler is selected from LLZTO.

[0010] The present invention designs a molecular coordination-regulated PEO-based solid electrolyte film, using PEO as a polymer matrix, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) as a lithium salt, lithium lanthanum zirconium tantalum oxide nanoparticles (LLZTO) as an inorganic filler, and lithium difluorobis(oxalyl)phosphate (DFBOP) as a molecular coordination regulator. The inventors found in experiments that LiTFSI has a low lattice energy and can dissociate well, releasing enough free Li + , improving the ionic conductivity of PEO-based solid electrolytes. In addition, inorganic components such as LiF and Li3N generated by decomposition at the interface are beneficial to improving interface stability. Compared with LiTFSI, DFBOP has a relatively high Li + Binding energy and stronger Li + affinity, which can promote the dissociation of LiTFSI and increase the free Li + In addition, the narrow LUMO-HOMO energy gap of DFBOP is conducive to its preferential decomposition on the positive and negative electrode surfaces, forming a dense and strong interface layer. At the same time, the coordination coupling between DFBOP and LiTFSI and PEO can further promote the synergistic decomposition of LiTFSI-DFBOP to form a LiF-rich x PO y F z and the interface layer of PO components. Therefore, through the effective regulation of the molecular coordination in the electrolyte, a dense and strong inorganic-rich SEI and CEI film is constructed on the electrolyte / electrode surface, which promotes the uniform deposition of lithium, inhibits the growth of lithium dendrites and accelerates the interface reaction kinetics, and inhibits the violent decomposition of PEO at the electrode interface on the other hand, and improves the long-term stability of the electrolyte / electrode interface. The use of LLZTO nanoparticles as inorganic fillers can further disrupt the ordering of PEO segments, reduce its crystallinity, and promote the dissociation of LiTFSI, forming a new ion conduction path, and increasing the ionic conductivity and mechanical properties of the electrolyte. Thanks to this, the solid-state lithium metal battery using the electrolyte exhibits excellent electrochemical performance and cycle stability. It can be seen that the combination of PEO-LiTFSI-DFBOP-LLZTO disclosed in the present invention is indispensable and cannot be replaced by conventional types in the art. It has been found through experiments that if LiTFSI is partially replaced with lithium salt-lithium hexafluorophosphate, which is common in the art, the cycle stability will decrease.

[0011] Preferred:

[0012] The molar ratio of PEO to LiTFSI is (12-18):1;

[0013] Based on the total mass of the PEO-based solid electrolyte film, the mass fraction of the molecular coordination regulator is (0.1-4.0)%, and the mass fraction of the filler is (5-15)%.

[0014] Further preferred:

[0015] The molar ratio of PEO to LiTFSI is 16:1;

[0016] Based on the total mass of the PEO-based solid electrolyte film, the mass fraction of the molecular coordination regulator is 2%, and the mass fraction of the filler is 10%.

[0017] In the present invention, the LLZTO has a cubic garnet structure and can be prepared by a solid phase sintering method and a high energy ball milling method.

[0018] The present invention also discloses a method for preparing the PEO-based solid electrolyte film, which specifically comprises:

[0019] S1. LiTFSI, DFBOP and LLZTO are mixed with a solvent and subjected to ultrasonic treatment to obtain a suspension A;

[0020] S2. Weigh PEO and add it to the suspension A, mix well to obtain electrolyte slurry B;

[0021] S3. Casting the electrolyte slurry B onto a mold in an anhydrous and oxygen-free environment, and obtaining a PEO-based solid electrolyte membrane after the solvent evaporates.

[0022] In step S1:

[0023] The solvent is selected from one or more of acetonitrile, DMF and acetone;

[0024] The concentration of lithium salt in the solvent is 0.01-0.03 g / mL.

[0025] In step S2:

[0026] The mass ratio of PEO to the solvent added in step S1 is 1: (12-16);

[0027] Preferably, the electrolyte slurry B is further subjected to ultrasonic treatment before casting to fully remove bubbles in the electrolyte slurry B.

[0028] In step S3:

[0029] The anhydrous state means H2O≤0.1ppm, and the oxygen-free state means O2≤0.1ppm. The operation can be carried out in a glove box.

[0030] The present invention also discloses a solid-state lithium metal battery, comprising a negative electrode, a positive electrode and a PEO-based solid electrolyte membrane regulated by the molecular coordination of the present invention.

[0031] The negative electrode is selected from lithium metal;

[0032] The positive electrode is selected from lithium iron phosphate and / or lithium nickel cobalt manganese oxide (NCM811).

[0033] Compared with the prior art, the present invention has the following advantages:

[0034] 1. The present invention designs a PEO-based solid electrolyte film, and DFBOP is used as a molecular coordination regulator to regulate the PEO-Li in the electrolyte bulk phase. + Li + -TFSI - The interaction between PEO and LiO contributes to the improvement of the ion transport performance of the electrolyte. + On the other hand, the strong Lewis acid-base interaction between DFBOP and LiTFSI can promote the further dissociation of LiTFSI and increase the free Li + concentration, and at the same time, the PEO chain - The adsorption and anchoring effect hinders TFSI - The transport of anions and the increase of the ion transfer number of the electrolyte. Therefore, the ionic conductivity of the electrolyte and the rate performance of the battery are improved.

[0035] 2. The PEO-based solid electrolyte provided by the present invention has good lithium stability, and the critical current density can reach 1.1 mA / cm 2 , which can maintain the long-term stability of the Li / electrolyte interface structure. The coordination between DFBOP and LiTFSI promotes their synergistic decomposition at the lithium negative electrode interface to form a LiF-rich, Li x PO y F z , Li2C2O4 and Li3N SEI film, promoting the uniform deposition of lithium and effectively inhibiting the growth of lithium dendrites, thereby ensuring the long-term stable cycle of the battery.

[0036] 3. The PEO-based solid electrolyte provided by the present invention has good high-voltage stability, and the electrochemical window can reach 4.5V (vs. Li + / Li), which can maintain the long-term stability of the electrolyte / cathode interface structure. The dipole-dipole interaction between DFBOP and PEO can effectively reduce the HOMO energy level of PEO and inhibit its violent oxidative decomposition under high pressure. At the same time, the synergistic decomposition of DFBOP-LiTFSI promotes thex PO y F z The formation of CEI of inorganic components such as PO and others reduces the accumulation of by-products at the cathode interface and improves the structural stability of the NCM811 cathode, thereby ensuring the excellent electrochemical performance of the battery.

[0037] 4. The PEO-based solid electrolyte designed by the present invention can be well adapted to commercial cathode materials such as lithium iron phosphate and lithium nickel cobalt manganese oxide, and achieve excellent rate performance and cycle stability at an operating temperature of 60°C. The lithium iron phosphate battery using the above electrolyte can stably cycle 400 times at 1C, with a capacity retention rate of more than 90%, and has a high coulombic efficiency of 99.95%; the nickel cobalt manganese oxide battery using the above electrolyte can still stably cycle 100 times at 0.2C and a high cut-off voltage of 4.5V, and the coulombic efficiency reaches more than 99%.

[0038] 5. The preparation process of the PEO-based solid electrolyte provided by the present invention is simple, the mass ratio of the DFBOP additive used in the electrolyte is below 4wt.%, the preparation cost is low, and it is well compatible with the existing lithium-ion battery manufacturing process, and has great potential for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The cycle performance of the lithium iron phosphate batteries assembled in Example 3 and Comparative Example 3 respectively under 60°C and 1C working conditions;

[0040] Figure 2 The rate performance of the lithium iron phosphate batteries respectively assembled in Example 3 and Comparative Example 3 under the working condition of 60°C;

[0041] Figure 3 The cycle performance of the nickel cobalt manganese oxide lithium battery assembled in Example 4 and Comparative Example 4 under the working conditions of 60°C and 0.2C;

[0042] Figure 4 The PEO-based lithium metal symmetric cells assembled in Example 1 and Comparative Example 5 were tested at 60°C and 0.2 mA / cm 2 Cyclic performance testing under working conditions. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0044] Example 1

[0045] S1. Add 0.25 g LiTFSI, 0.1 g LLZTO and 0.02 g DFBOP additive to 12 mL anhydrous acetonitrile, dissolve and mix well, and then ultrasonically treat for 10 min to obtain a white suspension A;

[0046] The preparation of LLZTO in this embodiment is specifically as follows:

[0047] The raw materials of LiOH, La(OH)3, ZrO2 and Ta2O5 with a certain stoichiometric ratio are ball-milled at 600rpm / 1h, and then solid-phase sintering is performed after the mixture is evenly mixed. The solid-phase sintering is a high-temperature two-stage sintering, with sintering parameters of 950℃ / 8h and 1150℃ / 8h, and a heating rate of 10℃ / min. In order to prevent the volatilization of the lithium source during the sintering process, the LiOH raw material needs to be excessively

[0048] 10wt.%. After sintering, LLZTO powder with a cubic phase structure was obtained, and then high-energy ball milling at 1000rpm / 1h was performed to further refine the LLZTO particles to nanometer size (100nm).

[0049] S2. Weigh 0.6 g of PEO powder (EO: Li + =16:1) was added to the white suspension A, mixed evenly and stirred at room temperature for 24 h to obtain a uniform milky white electrolyte slurry B;

[0050] S3. The obtained electrolyte slurry B was ultrasonically treated for 10 min to remove bubbles in the electrolyte slurry;

[0051] S4. In a glove box (H2O≤0.1ppm, O2≤0.1ppm), the electrolyte slurry B was cast onto a polytetrafluoroethylene mold and allowed to stand for 12 hours to remove the anhydrous acetonitrile solvent. After the solvent evaporated completely, a PEO-based solid electrolyte membrane with a smooth surface was obtained, and the thickness of the membrane was 50-70μm. The obtained electrolyte membrane was cut into original sheets with a diameter of 20mm for standby use.

[0052] S5. The PEO-based solid electrolyte membrane prepared in this embodiment is assembled with a working electrode and a reference electrode in a glove box filled with argon atmosphere (H2O≤0.1ppm, O2≤0.1ppm) using a 2032-type battery shell to obtain a PEO-based lithium metal symmetric battery. Both the working electrode and the reference electrode are lithium metal, and the packaging pressure is 3MPa.

[0053] Comparative Example 1

[0054] The preparation process is substantially the same as that of Example 1, except that no DFBOP additive is added in step S1.

[0055] Example 2

[0056] Steps S1 to S4 are exactly the same as those in Example 1;

[0057] S5. The PEO-based solid electrolyte membrane prepared in this embodiment is assembled with the working electrode and the reference electrode in a glove box filled with argon atmosphere (H2O≤0.1ppm, O2≤0.1ppm) using a 2032-type battery shell to obtain a PEO-based lithium metal asymmetric battery. The working electrode is a stainless steel sheet, and the reference electrode is lithium metal. The packaging pressure is 3MPa.

[0058] Comparative Example 2

[0059] The preparation process is substantially the same as that of Example 2, except that no DFBOP additive is added in step S1.

[0060] Example 3

[0061] Steps S1 to S4 are exactly the same as those in Example 1;

[0062] S5. The PEO-based solid electrolyte membrane prepared in this embodiment is assembled with the positive electrode and the negative electrode in a glove box filled with argon atmosphere (H2O≤0.1ppm, O2≤0.1ppm) using a 2032-type battery shell to obtain a PEO-based solid-state lithium metal battery. The positive electrode material is lithium iron phosphate, and the negative electrode material is lithium metal, and the packaging pressure is 3MPa.

[0063] The positive electrode material is a mixture of positive electrode active material lithium iron phosphate, polyvinylidene fluoride (PVDF) binder and Super P conductive agent in a ratio of 8:1:1. The surface loading of the positive electrode active material is 2.5 mg / cm 2 .

[0064] Comparative Example 3

[0065] The preparation process is substantially the same as that of Example 3, except that no DFBOP additive is added in step S1.

[0066] Example 4

[0067] Steps S1 to S4 are exactly the same as those in Example 1;

[0068] S5. The PEO-based solid electrolyte membrane prepared in this embodiment is assembled with the positive electrode and the negative electrode in a glove box filled with argon atmosphere (H2O≤0.1ppm, O2≤0.1ppm) using a 2032-type battery shell to obtain a PEO-based solid-state lithium metal battery. The positive electrode material is lithium nickel cobalt manganese oxide, and the negative electrode material is lithium metal, and the packaging pressure is 3MPa.

[0069] The positive electrode material is a mixture of positive electrode active material lithium nickel cobalt manganese oxide, polyvinylidene fluoride (PVDF) binder and SuperP conductive agent in a ratio of 8:1:1. The surface loading of the positive electrode active material is 2.5 mg / cm 2 .

[0070] Comparative Example 4

[0071] The preparation process is substantially the same as that of Example 4, except that no DFBOP additive is added in step S1.

[0072] Comparative Example 5

[0073] The preparation process is basically the same as that of Example 1, except that in step S1, LiTFSI is replaced by LiTFSI and lithium hexafluorophosphate LiPF6 (the mass ratio of the two is 1:1, and the total mass is 0.25 g).

[0074] Performance Testing

[0075] 1. The critical current density test was performed on the batteries prepared in Example 1 and Comparative Example 1 at 60°C, and the electrochemical window test was performed on the batteries prepared in Example 2 and Comparative Example 2 at 60°C to determine the positive and negative electrode interface compatibility of the PEO-based solid electrolyte membrane. The specific test results are shown in Tables 1 and 2.

[0076] Table 1

[0077]

[0078] Table 2

[0079]

[0080] It can be found that compared with the comparative example, the PEO-based solid electrolyte membrane prepared by the embodiment of the present invention has a higher critical current density (1.1 mA / cm 2 ) and a wider electrochemical stability window (4.5 V), indicating its good lithium stability and high voltage compatibility, which can maintain the long-term stability of the Li / electrolyte and electrolyte / cathode interface structures.

[0081] 2. The cycle performance and rate performance of the PEO-based solid-state lithium metal batteries in Examples 3 to 4 and Comparative Examples 3 to 4 were tested at 60°C to determine the practicality of the PEO-based solid-state electrolyte. The specific test results are as follows: Figure 1 , Figure 2 and Figure 3 shown.

[0082] Figure 1 The cycle performance of the lithium iron phosphate battery in Example 3 and Comparative Example 3 at 60°C and 1C working conditions; Figure 2It is the rate performance of the lithium iron phosphate battery in Example 3 and Comparative Example 3 under the working condition of 60°C; Figure 3 It is the cycle performance of the nickel cobalt manganese oxide lithium battery in Example 4 and Comparative Example 4 under the working conditions of 60°C and 0.2C.

[0083] from Figures 1 to 3 It is not difficult to find that, compared with the comparative example, the lithium iron phosphate battery and the nickel cobalt manganese oxide battery assembled using the PEO-based solid electrolyte membrane prepared by the present invention have better rate performance and cycle stability. Specifically, the lithium iron phosphate battery assembled using the PEO-based solid electrolyte membrane prepared by the present invention can stably cycle 400 times at 1C, with a capacity retention rate of more than 90%, and has a high coulomb efficiency of 99.95%, without obvious short circuit phenomenon, such as Figure 1 As shown; the lithium iron phosphate battery assembled with the PEO-based solid electrolyte membrane prepared in the comparative example exhibited obvious short-circuit behavior at a rate higher than 0.3C, indicating poor lithium dendrite inhibition ability, such as Figure 2 In addition, the nickel cobalt manganese oxide battery in Example 4 of the present invention can still stably cycle 100 times even at 0.2C and a high cut-off voltage of 4.5V, and the coulombic efficiency reaches more than 99%, showing excellent electrochemical performance and interface stability, as shown in FIG. Figure 3 shown.

[0084] 3. At 60℃ and 0.2mA / cm 2 The cycle performance test of the PEO-based lithium metal symmetric battery in Example 1 and Comparative Example 5 is as follows. Figure 4 shown.

[0085] from Figure 4 It can be found that the lithium metal symmetric battery in Example 1 using a single LiTFSI salt has better cycle stability at 0.2 mA / cm 2 The current density can be stably cycled for more than 7000 hours, and the polarization voltage does not increase significantly, maintaining below 30mV, highlighting the good compatibility of the electrolyte in Example 1 with the lithium negative electrode; while the lithium symmetric metal battery in Comparative Example 5 using LiTFSI+LiPF6 double salt has a significant increase in polarization voltage after 2000 hours of cycling, indicating poor negative electrode interface stability. The above results further show that the electrolyte in Example 1 of the present invention has better applicability when the lithium salt is LiTFSI, and has good practical application potential.

[0086] In summary, the use of DFBOP as a molecular coordination additive can effectively regulate the PEO-Li + Li + -TFSI -interaction and electrolyte / electrode interface structure, and construct LiF-rich, Li x PO y F z The dense and strong interface layer of inorganic components such as PEO and PO promotes the uniform deposition of lithium, inhibits the disordered growth of lithium dendrites, and maintains the long-term stability of the electrolyte / electrode interface. In addition, the violent side decomposition reaction of the electrolyte at the interface is also effectively suppressed, which is conducive to the long-term stable operation of PEO-based solid-state lithium metal batteries.

[0087] The above descriptions are only some specific embodiments of the present invention. It should be pointed out that a person skilled in the art can make many modifications and improvements. All modifications and improvements that do not exceed the scope of protection of the present invention should be regarded as within the scope of protection of the present invention.

Claims

1. A PEO-based solid electrolyte film, the raw material composition includes a polymer matrix and a lithium salt, characterized in that: The polymer matrix is ​​selected from PEO, and the lithium salt is selected from LiTFSI; The raw materials of the PEO-based solid electrolyte film also include a molecular coordination regulator and a filler. The molecular coordination regulator is selected from DFBOP, and the filler is selected from LLZTO.

2. The PEO-based solid electrolyte film according to claim 1, characterized in that: The molar ratio of PEO to LiTFSI is (12-18):1; Based on the total mass of the raw materials, the mass fraction of the molecular coordination regulator is (0.1-4.0)%, and the mass fraction of the filler is (5-15)%.

3. The PEO-based solid electrolyte film according to claim 1, characterized in that: The LLZTO has a cubic garnet structure and is prepared by a solid phase sintering method and a high energy ball milling method.

4. The PEO-based solid electrolyte film according to any one of claims 1 to 3, characterized in that: The molar ratio of PEO to LiTFSI is 16:1; Based on the total mass of the raw materials, the mass fraction of the molecular coordination regulator is 2%, and the mass fraction of the filler is 10%.

5. A method for preparing a PEO-based solid electrolyte film according to any one of claims 1 to 4, characterized in that: Specifically include: S1. LiTFSI, DFBOP and LLZTO are mixed with a solvent and subjected to ultrasonic treatment to obtain a suspension A; S2. Weigh PEO and add it to the suspension A, mix well to obtain electrolyte slurry B; S3. Casting the electrolyte slurry B onto a mold in an anhydrous and oxygen-free environment, and obtaining a PEO-based solid electrolyte membrane after the solvent evaporates.

6. The method for preparing a PEO-based solid electrolyte film according to claim 5, characterized in that: In step S1: The solvent is selected from one or more of acetonitrile, DMF and acetone; The concentration of lithium salt in the solvent is 0.01-0.03 g / mL.

7. The method for preparing a PEO-based solid electrolyte film according to claim 5, characterized in that: In step S2: The mass ratio of PEO to the solvent added in step S1 is 1:(12-16).

8. The method for preparing a PEO-based solid electrolyte film according to claim 5, characterized in that: In step S3: The anhydrous state means H2O≤0.1ppm, and the oxygen-free state means O2≤0.1ppm.

9. A solid-state lithium metal battery, comprising a negative electrode, a positive electrode and an electrolyte membrane, characterized in that: A PEO-based solid electrolyte film according to any one of claims 1 to 4 is used.

10. The solid-state lithium metal battery according to claim 9, characterized in that: The negative electrode is selected from lithium metal; The positive electrode is selected from lithium iron phosphate and / or lithium nickel cobalt manganese oxide.

Citation Information

Cited By

  • PEO-based solid electrolyte membrane as well as preparation method and application thereof

    CN120280547A

  • Composite solid electrolyte taking lithium iron phosphate as filler as well as preparation method and application of composite solid electrolyte

    CN121565930A